EFEKTIVITAS MANAJEMEN TAHFIDZ AL-QUR’AN TERHADAP KUALITAS HAFALAN SANTRI KELAS XII DI MADRASAH ALIYAH PONDOK PESANTREN TAHFIDZUL QUR’AN AL-IMAM ASHIM MAKASSAR: Penelitian Mixmethods - nur azizah, azizah; Mstamin, Mustamin; zainal, Abdul Qahar; wahab, abdul; Azhar, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the effectiveness of Quran memorization management on the quality of memorization among 12th-grade students at the Tahfidzul Qur'an Al-Imam Ashim Islamic Boarding School in Makassar. Using a mixed-methods approach, the research combines qualitative interviews with pesantren administrators and teachers, as well as quantitative assessments of students’ memorization outcomes. The findings show that effective planning, structured implementation, and continuous evaluation significantly support the quality of Quran memorization. Key supporting factors include discipline, intrinsic motivation, and teacher guidance. However, challenges such as cognitive overload in final-year students and distractions from external activities were also identified. The results highlight that systematic management plays a crucial role in sustaining the fluency, tajweed accuracy, and consistency of students' memorization.